Identification of Epigenetic Targets in Prostate Cancer for Therapeutic Development - Björkman, Mari (Annales Universitatis Turkuensis D 1057, 2013)
Recurrent castration resistant prostate cancer remains a challenge for cancer therapies and novel treatment options in addition to current anti-androgen and mitosis inhibitors are needed. Aberrations in epigenetic enzymes and chromatin binding proteins have been linked to prostate cancer and they may form a novel class of drug targets in the future. In this thesis we systematically evaluated the epigenenome as a prostate cancer drug target. We functionally silenced 615 known and putative epigenetically active protein coding genes in prostate cancer cell lines using high throughput RNAi screening and evaluated the effects on cell proliferation, androgen receptor (AR) expression and histone patterns. Histone deacetylases (HDACs) were found to regulate AR expression. Furthermore, HDAC inhibitors reduced AR signaling and inhibited synergistically with androgen deprivation prostate cancer cell proliferation. In particular, TMPRSS2- EGR fusion gene positive prostate cancer cell lines were sensitive to combined HDAC and AR inhibition, which may partly be related to the dependency of a fusion gene induced epigenetic pathway. Histone demethylases (HDMs) were identified to regulate prostate cancer cell line proliferation. We discovered a novel histone JmjC-domain histone demethylase PHF8 to be highly expressed in high grade prostate cancers and mediate cell proliferation, migration and invasion in in vitro models. Additionally, we explored novel HDM inhibitor chemical structures using virtual screening methods. The structures best fitting to the active pocket of KDM4A were tested for enzyme inhibition and prostate cancer cell proliferation activity in vitro. In conclusion, our results show that prostate cancer may efficiently be targeted with combined AR and HDAC inhibition which is also currently being tested in clinical trials. HDMs were identified as another feasible novel drug target class. Future studies in representative animal models and development of specific inhibitors may reveal HDMs full potential in prostate cancer therapy